2022
DOI: 10.3390/cells11223558
|View full text |Cite
|
Sign up to set email alerts
|

The CRK5 and WRKY53 Are Conditional Regulators of Senescence and Stomatal Conductance in Arabidopsis

Abstract: In Arabidopsis thaliana, cysteine-rich receptor-like kinases (CRKs) constitute a large group of membrane-localized proteins which perceive external stimuli and transduce the signal into the cell. Previous reports based on their loss-of-function phenotypes and expression profile support their role in many developmental and stress-responsive pathways. Our study revealed that one member of this family, CRK5, acts as a negative regulator of leaf aging. Enrichment of the CRK5 promoter region in W-box cis-elements d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…ORS278 in A. thaliana. WRKY50 and ZAT10 were previously indicated by Taki et al [150] as OPDA-specific response genes, and were also found to be related to plant salt stress response [155,156].…”
Section: Hormonal Modulationmentioning
confidence: 80%
“…ORS278 in A. thaliana. WRKY50 and ZAT10 were previously indicated by Taki et al [150] as OPDA-specific response genes, and were also found to be related to plant salt stress response [155,156].…”
Section: Hormonal Modulationmentioning
confidence: 80%
“…However, the mechanisms underlying drought tolerance and the molecular pathways involved in drought stress sensing and cellular responses remain largely unknown. RLKs perceive the majority of internal and external stimuli in plants, and CRKs play important roles in plant development, responses to biotic and abiotic stress (including drought stress) (Bourdais et al, 2015; Burdiak et al, 2022; Chen et al, 2004; Hunter et al, 2019; Yeh et al, 2015; Zhao et al, 2022), making them promising candidates for manipulating stress‐response pathways. Here, we present molecular evidence that CRK4 and CRK14, which showed differential expression between Col‐0 and L er ‐0, positively and negatively regulate, respectively, ABA‐mediated stomatal movements and drought stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…WRKYs positively or negatively regulate leaf senescence depending on their diverse target genes. In Arabidopsis, AtWRKY6, AtWRKY53, AtWRKY55, and AtWRKY71 can directly target and activate the expressions of receptor-like protein kinase genes, senescence-induced receptor-like kinase ( SIRK ) and cysteine-rich receptor-like kinase 5 ( CRK5 ), or SAGs, senescence-associated gene 13 ( SAG13 ), senescence-associated gene 201 ( SAG201 ), and stay-green ( SGR ), to positively influence senescence ( Robatzek and Somssich 2002 ; Zhang et al 2018 ; Wang et al 2020 ; Yu et al 2021 ; Burdiak et al 2022 ). In rice, OsWRKY42 binds to the rice Metallothionein 1d ( OsMT1d ) promoter and represses its expression to promote senescence ( Han et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%